THE EFFECTIVENESS OF YOUTUBE VIDEO TO IMPROVE STUDENTS’ GRAMMAR ABILITY - Hanna Safira Delyuzar; Aseptiana Parmawati (IKIP Siliwangi, 2024)
YouTube is the world’s considerable and most influential footage website. Students who use YouTube will be easier to get the information in learning. The aims of the research was to get on a significant outgrowth of utilize YouTube video to improve the students’ grammar ability. This research was quantitative, and it was conducted using a pre-experimental design, specifically a pre-test-post-test design with one group. The study focus was on seventh-grade students from Cimahi Junior High Schools in academic year 2020/2021 with a total sample was 36 students. In gathering data, the researcher used test and SPSS system to assay the contain data. The outcome revealed that value with data of post-test that mean score of pre-experimental post-test (88,75) was considerable than pre-test (72,50), and the worth of the paired T-test (0.000) was underneath than 0.05. In other words, the alternative hypothesis (Ha) was accepted because the method of learning YouTube video significant to improve students’ grammar ability.